The Information Content of FAS 33 Returns on Equity. - Murdoch, Brock (The Accounting Review, 1986)
ABSTRACT: This research examines the ability of FAS 33 returns on equity to explain security returns. Initially, the ability of FAS 33 returns to add to the explanatory power of historical cost returns is assessed. Subsequently, the ability of historical cost returns to add to the explanatory power of FAS 33 returns on equity is evaluated. Data for 1980, 1981, and 1982 are analyzed. A matched-pair design is used to control for the effects of cross-sectional correlation on the dependent and independent variables. Four versions of FAS 33 returns on equity -are tested. Results indicate that constant dollar, current cost, and net holding returns do not demonstrate information content incremental to historical cost returns in explaining security price changes.. Purchasing power returns on equity, however, 'are shown to possess incremental' information content. Furthermore, results indicate that while historical cost returns on equity do increase the ability of constant dollar, purchasing power, and net holding returns on equity to explain security price changes, historical cost returns do not increase the explanatory power of current cost returns on equity,